Infiltrating Blood-Derived Macrophages Are Vital Cells Playing an Anti-inflammatory Role in Recovery from Spinal Cord Injury in Mice - Shechter, Ravid; London, Anat; Varol, Chen; Raposo, Catarina; Cusimano, Melania; Yovel, Gili; Rolls, Asya; Mack, Matthias; Pluchino, Stefano; Martino, Gianvito; Jung, Steffen; Schwartz, Michal (PLoS medicine, 2009)
Although macrophages (MPhi) are known as essential players in wound healing, their contribution to recovery from spinal cord injury (SCI) is a subject of debate. The difficulties in distinguishing between different MPhi subpopulations at the lesion site have further contributed to the controversy and led to the common view of MPhi as functionally homogenous. Given the massive accumulation in the injured spinal cord of activated resident microglia, which are the native immune occupants of the central nervous system (CNS), the recruitment of additional infiltrating monocytes from the peripheral blood seems puzzling. A key question that remains is whether the infiltrating monocyte-derived MPhi contribute to repair, or represent an unavoidable detrimental response. The hypothesis of the current study is that a specific population of infiltrating monocyte-derived MPhi is functionally distinct from the inflammatory resident microglia and is essential for recovery from SCI. We inflicted SCI in adult mice, and tested the effect of infiltrating monocyte-derived MPhi on the recovery process. Adoptive transfer experiments and bone marrow chimeras were used to functionally distinguish between the resident microglia and the infiltrating monocyte-derived MPhi. We followed the infiltration of the monocyte-derived MPhi to the injured site and characterized their spatial distribution and phenotype. Increasing the naïve monocyte pool by either adoptive transfer or CNS-specific vaccination resulted in a higher number of spontaneously recruited cells and improved recovery. Selective ablation of infiltrating monocyte-derived MPhi following SCI while sparing the resident microglia, using either antibody-mediated depletion or conditional ablation by diphtheria toxin, impaired recovery. Reconstitution of the peripheral blood with monocytes resistant to ablation restored the lost motor functions. Importantly, the infiltrating monocyte-derived MPhi displayed a local anti-inflammatory beneficial role, which was critically dependent upon their expression of interleukin 10. The results of this study attribute a novel anti-inflammatory role to a unique subset of infiltrating monocyte-derived MPhi in SCI recovery, which cannot be provided by the activated resident microglia. According to our results, limited recovery following SCI can be attributed in part to the inadequate, untimely, spontaneous recruitment of monocytes. This process is amenable to boosting either by active vaccination with a myelin-derived altered peptide ligand, which indicates involvement of adaptive immunity in monocyte recruitment, or by augmenting the naïve monocyte pool in the peripheral blood. Thus, our study sheds new light on the long-held debate regarding the contribution of MPhi to recovery from CNS injuries, and has potentially far-reaching therapeutic implications.